2019
DOI: 10.1155/2019/2054846
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Safety of Percutaneous Dilational Tracheostomy Compared with Surgical Tracheostomy in the Intensive Care Unit

Abstract: Background Tracheostomy is a necessary procedure for patients who require long-term mechanical ventilation support. There are two methods for tracheostomy in current use: surgical tracheostomy (ST) and percutaneous dilational tracheostomy (PDT). In the current study, we retrospectively compared the safety of both procedures performed in our intensive care unit (ICU). Methods In this study, we enrolled subjects who underwent tracheostomy in our ICU between January 2012 and March 2016. We excluded subjects who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(10 reference statements)
2
4
0
Order By: Relevance
“…For example, a cohort study by Suzuki et al found rates of all complications to be lower in the PT group when compared to the non-PT group, including infection and air leak, consistent with our findings. 24 A Cochrane review by Brass et al found decreased risk of complications such as infection and tracheoesophageal fistula formation in PT patients but no difference in bleeding complications, further corroborating our results. 13 Additionally, there were five causes of tracheostomy-related deaths in the LT group, compared to just one (hemorrhage) in the ET group.…”
Section: Discussionsupporting
confidence: 90%
“…For example, a cohort study by Suzuki et al found rates of all complications to be lower in the PT group when compared to the non-PT group, including infection and air leak, consistent with our findings. 24 A Cochrane review by Brass et al found decreased risk of complications such as infection and tracheoesophageal fistula formation in PT patients but no difference in bleeding complications, further corroborating our results. 13 Additionally, there were five causes of tracheostomy-related deaths in the LT group, compared to just one (hemorrhage) in the ET group.…”
Section: Discussionsupporting
confidence: 90%
“…32 The teams at LAC and Keck Hospital are multidisciplinary, with the participation of the ICU nurse and respiratory therapy during the surgery and the intensivist and speech language pathologists postoperatively. Regarding long-term complications, some studies state that PDT has a lower complication rate than OBT, 4,31 while other studies note that PDT has more complications. 7,33 We believe that these conflicting data are due to the lack of long-term followup with patients after tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the current literature, which shows similar intraoperative complications among all 3 modalities. 25,30,31 The data for long-term postoperative complications for PDT vs OR tracheostomy and OBT are more controversial. For complications within 7 days, multiple studies support the finding that PDT and OBT have similar complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…PDT leads to a close fitting of the tracheal cannula to the stoma; humid wound conditions are sporadic. Suzuki et al concluded in their study that the small skin incision during the PDT procedure leads to fewer postoperative complications and is, therefore, a safer procedure than OST to be performed in ICU [ 24 ].…”
Section: Discussionmentioning
confidence: 99%